Genetic algorithms for a robust 3-D MR-CT registration. - Rouet, J.-M (IEEE Transactions on information technology in biomedicine)
Presents an original usage of genetic algorithms as a robust search space sampler in an application to 3D medical image elastic registration. An overview of the standard steps of a registration algorithm is given. We focus on the genetic algorithm use, and particularly on the problem of extracting the optimal solution among the final genetic population. We provide an original encoding scheme relying on a structural approach of point matching and then point out the need for a local optimization process. We then illustrate the algorithm with a concrete registration example and assert the results with a direct multi-volume rendering tool. Finally, the algorithm is applied to the Vanderbilt medical image database to assert its robustness and in order to compare it with other techniques.